FORMATION OF EMOTIONAL STABILITY IN PRESCHOOL CHILDREN IN FAMILY EDUCATION: THE IMPORTANCE OF MUSIC THERAPY (Universal International Scientific Journal, 2026)
This thesis covers the issues of forming emotional stability in preschool children in the context of family upbringing. In the course of the research, the role of the family in the emotional development of children, the importance of the educational environment, and the pedagogical possibilities of music therapy are analyzed. Also, the positive impact of music on children's psyche, its role in strengthening emotional balance, and ways of its use in the process of family upbringing are widely analyzed.
Keywords: emotional stability; preschool age; family upbringing